An Integrative Genomic Island Affects the Adaptations of the Piezophilic Hyperthermophilic Archaeon Pyrococcus yayanosii to High Temperature and High Hydrostatic Pressure - Li, Zhen; Li, Xuegong; Xiao, Xiang; Xu, Jun (Frontiers in Microbiology, 2016)
Deep-sea hydrothermal vent environments are characterized by high hydrostatic pressure and sharp temperature and chemical gradients. Horizontal gene transfer is thought to play an important role in the microbial adaptation to such an extreme environment. In this study, a 21.4-kb DNA fragment was identified as a genomic island, designated PYG1, in the genomic sequence of the piezophilic hyperthermophile Pyrococcus yayanosii. According to the sequence alignment and functional annotation, the genes in PYG1 could tentatively be divided into five modules, with functions related to mobility, DNA repair, metabolic processes and the toxin-antitoxin system. Integrase can mediate the site-specific integration and excision of PYG1 in the chromosome of P. yayanosii A1. Gene replacement of PYG1 with a SimR cassette was successful. The growth of the mutant strain ∆PYG1 was compared with its parent strain P. yayanosii A2 under various stress conditions, including different pH, salinity, temperature and hydrostatic pressure. The ∆PYG1 mutant strain showed reduced growth when grown at 100 °C, while the biomass of ∆PYG1 increased significantly when cultured at 80 MPa. Differential expression of the genes in module Ⅲ of PYG1 was observed under different temperature and pressure conditions. This study demonstrates the first example of an archaeal integrative genomic island that could affect the adaptation of the hyperthermophilic piezophile P. yayanosii to high temperature and high hydrostatic pressure.